Unlocking Testosterone Production by Biotransformation: Engineering a Fungal Model of Aspergillus nidulans Strain Deficient in Steroid 11α-Hydroxylase Activity and Expressing 17β-Hydroxysteroid Dehydrogenase Enzyme as Proof of Concept - Lidia Ortega-de los Ríos; Luis Getino; Beatriz Galán; José Luis García; José M. Luengo; Alejandro Chamizo-Ampudia; José M. Fernández-Cañón (Biomolecules)
Testosterone holds significant medical and economic importance, with the global market for testosterone replacement therapies valued at approximately USD 1.9 billion in 2023. This hormone is essential for the development and maintenance of male sexual characteristics as well as bone and muscle health. It plays a key role in conditions such as hypogonadism, muscle disorders, and andropause. However, the industrial production of testosterone often involves complex chemical processes that result in low yields, high costs, and environmental damage. Microbial biotransformation of steroids presents an eco-friendly alternative to traditional chemical synthesis. A knockout strain of Aspergillus nidulans deficient in steroid 11α-hydroxylase activity was developed, rendering it incapable of hydroxylating androstenedione, progesterone, and testosterone. In these strains, two newly identified CYP450 enzymes, CYP68L1 from A. nidulans and CYP68L8 from Aspergillus ochraceus, were expressed to confirm their roles as steroid 11α-hydroxylases of androstenedione, progesterone, and testosterone. The availability of these 11α-hydroxylases represents significant progress toward achieving efficient single-step steroid fermentation. Furthermore, the A. nidulans knockout strain serves as an effective model for studying the conversion of androstenedione to testosterone upon the expression of the enzyme 17β-hydroxysteroid dehydrogenase, due to its inability to hydroxylate testosterone.